Influence of anodizing voltage on formation of Porous Anodic Aluminium Oxide thin films in mixed solution of H3PO4 and CH3COOH - Juyana, A. Wahab; Mohd. Nazree, Derman; A.H, Iqwan (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.